2022
DOI: 10.1111/aab.12794
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of wood distillate boosts plant yield and nutritional parameters of chickpea

Abstract: In the quest for eco-friendly products with biostimulant properties, foliar application of wood distillate (WD) was tested on the growth and yield of chickpea (Cicer arietinum L.). WD (pyroligneous acid) is a by-product of plant biomass pyrolysis and is rich in biologically active substances like polyphenols, alcohols, acids and esters. In this work, chickpea plants were sprayed weekly with 100 ml 0.25% (v/v) chestnut (Castanea sativa Mill.) WD during the whole growing period, and at the end physiological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…These data demonstrate that the WD treatment can promote higher sugar content in the product, resulting in a tastier outcome without the need for any genetic editing. Moreover, a higher concentration of polyphenols was observed, as previously reported for chickpea seeds (Fedeli, Vannini, Celletti, et al, 2023), tomato (Rose et al, 2016), and strawberry fruits (Kårlund et al, 2014), following an application of 0.2%-0.5% WD. It is well known that lycopene is one of the most relevant and characteristic molecules of tomato, as it is found in much higher levels than other fruits (i.e., watermelon, pink grapefruit, and apricot).…”
Section: Quality Parameterssupporting
confidence: 83%
“…These data demonstrate that the WD treatment can promote higher sugar content in the product, resulting in a tastier outcome without the need for any genetic editing. Moreover, a higher concentration of polyphenols was observed, as previously reported for chickpea seeds (Fedeli, Vannini, Celletti, et al, 2023), tomato (Rose et al, 2016), and strawberry fruits (Kårlund et al, 2014), following an application of 0.2%-0.5% WD. It is well known that lycopene is one of the most relevant and characteristic molecules of tomato, as it is found in much higher levels than other fruits (i.e., watermelon, pink grapefruit, and apricot).…”
Section: Quality Parameterssupporting
confidence: 83%
“…(Dou et al, 2012), eggplant ( Solanum melongena L.) (Zhou et al, 2013), tomato ( Solanum lycopersicum L.) (Zhou et al, 2011) and black pepper ( Piper nigrum L.) (Jeong et al, 2006). This significant increase in sugars could reflect the general well‐being of the plant, as it has been hypothesized that an increase in soluble sugar content is likely related to an increase in photosynthetic performance and subsequent plant yield (Fedeli, Vannini, Celletti, et al, 2022). These considerations are supported by scientific evidence showing that in plants WD stimulates chlorophyll production and photosynthetic activity, as reported for several crop species, with important positive consequences on the fruits (Berahim et al, 2014; Grewal et al, 2018; Theerakulpisut et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…WD is a by‐product of the pyrolysis of waste plant biomass used for bioenergy production (Grewal et al, 2018). Recent literature has given evidence of the biostimulant effects of WD on crop plants (Fedeli, Vannini, Celletti, et al, 2022; Mungkunkamchao et al, 2013; Ofoe et al, 2022; Yuan et al, 2022), as a result of its >200 biologically active compounds (Wei et al, 2010). Furthermore, the use of WD has been shown to be safe for humans (Filippelli et al, 2021) and sensitive non‐target organisms such as lichen, moss and fern, as well as for arable plants growing with crops (Fačkovcová et al, 2020a, 2020b; Fanfarillo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, De Costa et al [ 14 ] found a linear relationship between pod yield and leaf area duration, and the seed yield was correlated with the number of pod-bearing nodes. Moreover, Fedeli et al [ 56 ] reported that chickpeas receiving WD as foliar spray over the entire growth cycle did not change the vegetative biomass compared to untreated plants but increased the mean weight and nutritional quality of seed, thus demonstrating a positive effect on the seed-filling process.…”
Section: Discussionmentioning
confidence: 99%